A Sociological Study on the Impact of Social Media on the Socio-Political Life of Youth in DG Khan (Al-Aasar, 2025)
This study investigates the transformative impact of social media on the socio-political life of youth in DG Khan, a developing district in South Punjab, Pakistan. Drawing from sociological theory and grounded in empirical evidence, the article explores how platforms such as Facebook, Twitter, WhatsApp, and YouTube have become essential tools for political socialization, civic participation, and digital activism among youth. By integrating Media Dependency Theory, Uses and Gratification Theory, and the Civic Voluntarism Model, the study illustrates how youth utilize social media not only for entertainment but also for expressing political opinions, mobilizing support, and holding political leaders accountable. Findings indicate that social media enhances political knowledge, civic responsibility, and political competency, contributing to the democratization of political discourse in underserved regions. However, the study also identifies several challenges, including digital inequality, misinformation, political polarization, and psychological risks such as anxiety and low self-esteem. The dual nature of social media—as both an empowering and potentially harmful tool—is examined in the context of youth behavior, online culture, and access disparities. This article concludes by emphasizing the need for critical media literacy and regulatory oversight to maximize the benefits of social media while minimizing its risks.